Vers des convergences interdisciplinaires dans le champ des études électorales ? - Joël Gombin; Jean Rivière (L'Espace Politique)
Introductory article of the issue 23 (2014-2) of the journal L’Espace politique entitled "Electoral Geography and Sociology: Duel or Duo?"